Targeted modulation of gut microbiota by traditional Chinese medicine and natural products for liver disease therapy - Zhu, Li-Ran; Li, Shan-Shan; Zheng, Wan-Qun; Ni, Wei-Jian; Cai, Ming; Liu, Hai-Peng (Frontiers in Immunology, 2023)
The gut microbiota not only constitutes intestinal microenvironment homeostasis and human health but also exerts indispensable roles in the occurrence and progression of multiple liver diseases, including alcohol-related liver disease, nonalcoholic fatty liver disease, autoimmune liver disease and liver cancer. Given the therapeutic status of these diseases, their prevention and early therapy are crucial, and the detailed mechanism of gut microbiota in liver disease urgently needs to be explored. Meanwhile, multiple studies have shown that various traditional Chinese medicines, such as Si Miao Formula, Jiangzhi Granules, Liushen Capsules, Chaihu-Shugan Power, Cassiae Semen and Gynostemma, as well as some natural products, including Costunolide, Coprinus comatus polysaccharide, Antarctic krill oil, Oridonin and Berberine, can repair liver injury, improve fatty liver, regulate liver immunity, and even inhibit liver cancer through multiple targets, links, and pathways. Intriguingly, the aforementioned effects demonstrated by these traditional Chinese medicines and natural products have been shown to be closely related to the gut microbiota, directly driving the strategy of traditional Chinese medicines and natural products to regulate the gut microbiota as one of the breakthroughs in the treatment of liver diseases. Based on this, this review comprehensively summarizes and discusses the characteristics, functions and potential mechanisms of these medicines targeting gut microbiota during liver disease treatment. Research on the potential effects on gut microbiota and the regulatory mechanisms of traditional Chinese medicine and natural products provides novel insights and significant references for developing liver disease treatment strategies. In parallel, such explorations will enhance the comprehension of traditional Chinese medicine and natural products modulating gut microbiota during disease treatment, thus facilitating their clinical investigation and application.